Cassette Tape Revival as Creative Anachronism. Issue 1 (February 2017) - DEMERS, JOANNA
ABSTRACT: Listeners of a certain age tend to think that the cassette tape fell out of favour sometime during the 1990s, but is experiencing a revival of sorts as curious Millennials discover the pleasures of mixtapes and decaying media. But cassette tapes have been in constant use since their invention in 1963. Outside of North America and Western Europe, the tape is still the predominant phonographic medium, and is unseating hard drives as the preferred medium for data storage. For whom, then, is this a revival? My article argues that the tape revival is less an attempt at neutral recuperation of the past than a purposeful rewriting of history. Cassettes are particularly potent because they signify death and decay more forcefully even than vinyl. Their acoustic imperfections and mechanical frailties are now aestheticized in novels and contemporary popular music. Even curated listening experiences, from podcasts to streaming services, are designed to replicate the mixtape. The second era of the cassette tape represents another example of Simon Reynolds' concept of retromania, and can be fruitfully understood as a chapter in the evolving story of phonographic waste.